Bone Defects Following Trauma, Managed by Non-Vascularized Fibular Strut Graft: A Single Centre Study - Kumar, Sumedh; Sachdev, Tushar; Ratanpal, Ankush; Thakur, Aman; Pratap Singh, Bhanu; Ekka, Anuj Kumar (International Journal of Innovative Research in Medical Science, 2022)
Objective: Treatment of segmental bone loss is a challenge in orthopaedic practice. The purpose of our study is to evaluate results of non-vascularized fibula strut graft in patients treated for bone loss in femur and tibia bone defects. Methods: We prospectively evaluated 20 patients who have underwent non-vascularized fibular grafting as definitive treatment of post-traumatic bone defects of femur or tibia from January 2019 to October 2021. The pre-operative information including clinical and radiological examination to assess the condition of bone and to estimate the length of defect were collected and fibula graft of appropriate length was placed in the defect. Follow up results of the ranges of motion and limb length discrepancy were measured, and radiological outcome was assessed. All patients were followed up at 6 weeks, 3, 6 and 12 months. Results: Out of twenty patients only a single report of nonunion was noted. Union was achieved in 95% of our patients. Sixteen of our patients had good range of movement of knee and four patients had problem of knee stiffness. Six patients had shortening of 2cm. Two of our patients had superficial infection and one had deep infectivity an another had developed ankle stiffness and another one developed flap necrosis. Conclusion: Union rate of 95% and a near functional range of motion was seen in majority of our patients. Thus, we recommend use of non-vascularized fibula graft for open fracture with bone defect as it is simple, effective, inexpensive, technically less demanding with less donor site morbidity.